Influence of changes in alloying elements distribution and retained Austenite (RA) on mechanical properties of high boron alloy during quenching and partitioning(Q&P) process - Zhao Li; Run Wu; Shu-peng Song; Yu Wang; Teng Wu (Journal of Materials Research and Technology, 2022)
The quenching and partitioning (Q&P) process has been adopted innovatively to improve the toughness and wear resistance of Fe-0.44C-1.54B-3.97Mn-0.79Al-0.95Si alloy, and the microstructure, distribution of alloying elements, mechanical properties and dry sliding wear behavior of this alloy in as-cast and heat-treated by Q&P process were systematically investigated. The results show that test alloy consists mainly of martensite, retained austenite (RA) and eutectic boride phases. After being treated by Q&P process, the distribution of alloying elements in the microstructure becomes uniform and the impact toughness increases from 4.02 J cm-2 to 6.82 J cm-2, while the mass loss of the alloy is also decreased from 0.064 g to 0.051 g in dry sliding wear test. The improvement of the mechanical properties is attributed to the changes in the during Q&P process, especially the increase in the volume fraction of thin-film RA, as well as the fracture and spheroidization of part of the net-like boride.